Listen to Me: Transforming Learning Accessibility with an Audio-Based Android App for Visually Impaired Children - Pratiwi, Dian; Triraharjo, Bambang; Qori'ah, Aisyatul Vidyah; Surya, Ridho Pamungkas Ibnu; Aulia, Mega (Journal of Languages and Language Teaching, 2025)
This research aims to design and develop an audio-based Android application, Listen to Me app, specifically designed to support the learning needs of visually impaired children. The application seeks to enhance accessibility to educational content by providing audio-based materials, enabling users to engage with learning resources independently. The study adopts a Research and Development (RnD) approach, utilizing the Waterfall Method development model. This structured approach consists of four main stages: conducting a user needs analysis, designing the application, developing a prototype based on inclusive design principles, and testing the usability of the application with visually impaired children. Each stage is meticulously aligned with the goal of creating a user-friendly and effective learning tool. The findings reveal that the app significantly improves learning accessibility through its interactive features, such as voice-guided navigation and customizable audio content tailored to user preferences. These results highlight the potential of Listen to Me app to empower visually impaired children by fostering their independence in accessing and engaging with educational content. The primary contribution of this research is the development of an innovative and inclusive audio-based learning platform. It provides a technological solution that addresses the unique learning challenges faced by visually impaired children, offering them greater autonomy and opportunities in education.